MANAJEMEN KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH PADA ERA DIGITAL - Anggia Gustami, Belina (Penerbit Lafadz Jaya, 2025)
Problems that occur in the virtual coordination process as a communication medium have obstacles in reaching elderly educators. The purpose of this study is to uncover and analyze leadership approaches, leadership patterns, leadership achievement results and supporting factors as well as inhibiting factors of leadership patterns in Senior High Schools. The approach used in this study is qualitative with descriptive methods. The results of the study show that; first, the high school principal in his leadership uses a contingency/situational approach. This is because a leader's approach to his subordinates must be based on the situation and conditions he faces; Second, the leadership pattern he uses is a transformational leadership pattern. This can be seen from the leadership vision he developed, the changes felt by educators, education staff, and students, the level of trust given to educators and education staff, and the motivation given is not just material motivation; Third, the results achieved are the achievement of various achievements both intracurricular and extracurricular, and increased discipline, professionalism in the digital era that demands more creativity and innovation from educators and education staff in the digital era; Fourth, the supporting factors are human resources, the environment, and the local community around the school, while the inhibiting factors are problems arising from the leadership of the previous principal.